TECHNOLOGICAL ASPECTS OF PRESERVATION PROCESSIG Of EDIBlE SHELL FISHES III..FACTORS INFLUENCING THE KEEPING QUALITY OF CRAB (SCYLLA SERRATA) DURING FREEZING AND FROZEN STORAGE - GEORGE, CHINNAMA GEORGE (Fishery Technology, 2016)
The possible factors leading to the loss of flavour and generalquality of crab during freezing and frozen storage have beenstudied. The preprocess ice storage condition of the raw materialwas found to be one such important factor while the fresh frozencrab meat remained in good organoleptic condition for about51 weeks at -23Â°C, the 7 days iced material held frozen was foundto have a shelflife of about 21 weeks. The fall in myofibrillar proteinnoted during frozen storage together with the loss of myosin ATPaseactivity correlated well with the loss of organoleptic qualities.